Presupposition and [e]motion: the upgraded function and the semantics of the participle in the New Testament - Albuquerque, Roque N. (Peter Lang, 2019)
Participle as semantic presupposition -- Greek participles : modulation versus modality and mood -- Functions of the participle -- Semantics of the upgraded participle -- Examination of New Testament examples of the upgraded participle.